2013
DOI: 10.1111/pace.12112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Right Ventricular Nonapical Pacing on Cardiac Function: A Meta‐analysis of Randomized Controlled Trials

Abstract: This meta-analysis found that RVNA (mainly RVS) pacing exhibited satisfactory long-term lead performance compared with RVA pacing and demonstrated beneficial effects in improving LVEF after the 6-month follow-up. Furthermore, it proved superior to RVA pacing in terms of interventricular synchrony and cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
1
33
2
Order By: Relevance
“…Recently, Weizong et al have discovered similar interaction between Apo A-I and Dengue virus. The research group showed that Apo A-I is associated with the virus particles and preincubation of dengue virus with HDL enhances viral infection through a scavenger receptor-BI- (SR-BI-) mediated mechanism [96]. These findings may also provide a possible mechanism for the enhancement of T. cruzi infection by HDL (Figure 1(e)).…”
Section: T Cruzi Infection and Host Cholesterol Transport Pathwaysmentioning
confidence: 99%
“…Recently, Weizong et al have discovered similar interaction between Apo A-I and Dengue virus. The research group showed that Apo A-I is associated with the virus particles and preincubation of dengue virus with HDL enhances viral infection through a scavenger receptor-BI- (SR-BI-) mediated mechanism [96]. These findings may also provide a possible mechanism for the enhancement of T. cruzi infection by HDL (Figure 1(e)).…”
Section: T Cruzi Infection and Host Cholesterol Transport Pathwaysmentioning
confidence: 99%
“…[52][53][54][55] Direct His bundle and para-Hisian pacing may be considered for AV block with a narrow QRS if pacing is performed below the site of block. 56 An intermittent AV conduction disorder could be treated initially with traditional RV pacing using algorithms to minimize pacing, with consideration of a Bi-V upgrade when the block becomes permanent.…”
Section: Alternative Pacing Sitesmentioning
confidence: 99%
“…At one time, high hopes were placed on alternative sites of RV pacing, for example, pacing in the RV outflow tract rather than the apex, but results of the studies were discouraging. [76][77][78][79][80][81] The long-term effects of pacing RV sites (outflow tract or septum) other than the apex are unknown. Direct His bundle and paraHisian pacing are generally not applicable to patients with AV block.…”
Section: (1) Risk Versus Benefitmentioning
confidence: 99%